NANOSTROUCTOUROVANI THERMO-ELECTRIC MATERIALS (REVIEW) - Фреїк, Дмитро Михайлович; Лоп'янко, Михайло Антонович; Юрчишин, Ігор Костянтинович; Лисюк, Юрій Володимирович; Соколов, Олександр Леонідович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The review of the works devoted to the quantum size effects in materials of the brought dimension down is done, in particular: metals, semimetals and semiconductors. The special attention is spared to ability of material to achieve the simultaneous increase of coefficient of power and reduction of heat conductivity in one direction. Perspective semiconductor connections are explored for construction of over grate quantum points, wires, pits and nanostructuring composite.